Pengaruh Foktor-Faktor Total Quality Managemet Terhadap Peningkatan Mutu Pendidikan SMA Negeri di Surabaya - Feliks Anggia B.P (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2017)
This study talks about the Effect of Total Quality Managemet Factors on Improvingthe Quality of Secondary School Education in Surabaya. The research population is allteachers of Senior High School who have worked for 5 years at least. A sample of 150Teachers.Result of research: 1). From result of test "F" that variable = X1 = quality dimension; X2= Focus on learners; X3 = Leadership; X4 = Sustainability Improvement and X5 = HumanResource Management simultaneously influence Educational Quality Improvement, this issupported by the value of R Square (RÂ²) of 0.752 and F = 9.589 with Sig = 0.001 <= 0.05.2). From the result of t test (partial test), it can be concluded that from the 5 variables thathave partial influence is the Variable The quality dimension has the effect of 20.1% to theimprovement of the Quality of Education, and has the contribution value on the change ofEducation Quality improvement equal to = 4.1%. Variable X3 = Leadership has influenceof 33.1% to the improvement of Education Quality, and has contribution value on changeof Education Quality improvement = 11.0% with value of Sig 0.000 <= 0.05. TheContinuous Improvement Variable has an influence of 18.4% on the improvement ofEducation Quality h, and has contribution value on the change of Education Qualityimprovement in Surabaya State High School equal to = 0.034% with value of sig 0.000 <=0.05.Keywords: Total Quality Managemet, Quality Improvement of Education.